PERAN YAYASAN PANTI ASUHAN RIYAADLUL YATAAMAA TERHADAP PEMENUHAN HAK ANAK MEMPEROLEH PENDIDIKAN - Novita Novita; Dr. Mustari, M.Hum; Prof. Dr. Rifdan (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2019)
Abstract. This study aims to determine: 1) The role of the Orphanage Foundation towards the fulfillment of children's rights to obtain education at the Riyaadlul Yataamaa Orphanage Foundation, 2) the obstacles and supports faced in implementing the role of the Riyaadlul Yataamaa Orphanage Foundation in fulfilling the children's right to education. For this purpose, the researchers used data collection techniques through, documentation, observation, and interviews. The data that has been obtained from the research results are processed using qualitative analysis to determine the role of the Orphanage Foundation in Fulfilling the Right of Children to Get Education. The results showed that; 1) The role of the Riyaadlul Yataamaa Orphanage Foundation in the fulfillment of children's rights to education has been carried out well, marked by the fulfillment of education for foster children. 2) Barriers and Supports faced by the Orphanage in Implementing the Role of the Riyaadlul Yataamaa Orphanage Foundation in Fulfilling Children's Right to Get Education: a) Problems originating from each child's personality, b) Problems arising from the Funding Factor. And as for Supporting the implementation of the Role of the Orphanage Foundation: (1) Orphanage Management as a Substitute for the Role of Parents, (2) Orphanage Management as a motivator (motivation).Keywords: Foundation, Children's Rights, Education